Induce negative differential resistance in organic devices through a ferroelectric polymer - Rath, Arup Kumar; Pal, Amlan J. (Organic Electronics, 2009)
We report how ferroelectric materials induce negative differential resistance (NDR) in organic devices. Fluorescein, which exhibits semiconducting current–voltage characteristics, shows NDR effect in a ferroelectric matrix. Here, we vary the concentration of fluorescein in the ferroelectric matrix to study its effect on NDR. We also show how the degree of polarization controls NDR. We infer that under a suitable bias, the ferroelectric polymer becomes polarized to facilitate electron-injection in the device followed by a double-reduction of fluorescein molecules. From the capacitance–voltage measurements, we substantiate the role of polarization in inducing NDR effect in organic molecules.

Imprinted electrodes for enhanced light trapping in solution processed solar cells - Mihi, Agustin; Beck, Fiona J.; Lasanta, Tania; Rath, Arup Kumar; Konstantatos, Gerasimos (Advanced Materials, 2013)